2010
DOI: 10.1089/cell.2009.0032
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid EnhancesIn VitroDevelopment and Oct-3/4 Expression of Miniature Pig Somatic Cell Nuclear Transfer Embryos

Abstract: The present study was carried out to examine the effects of valproic acid (VPA), a histone deacetylase inhibitor, on in vitro development of miniature pig somatic cell nuclear transfer (SCNT) embryos and on expression of a mouse Oct-3/4 promoter-driven enhanced green fluorescent protein (EGFP) gene (EGFP expression only detected in Oct-3/4-expressing cells) introduced into donor cells for SCNT during their development. The addition of 4 mM VPA to embryo culture medium for 48 h after activation significantly (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
3
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 45 publications
4
57
3
2
Order By: Relevance
“…The production of cloned mice from both ME and AE cytoplasts also support our previous findings on the beneficial effects of VPA treatments for mouse cloning in the B6CBAF1 strain (Costa-Borges et al 2010). These beneficial effects, corroborated in miniature pig SCNT embryos (Miyoshi et al 2010), have recently been questioned by Ono et al (2010), who compared the effects of different HDACis on cloning BD129F1 mice. The discrepancy of results in the mouse species can be probably attributed to strain-specific differences, as not all HDACis are equally effective in all genetic backgrounds (Kishigami et al 2007, Van Thuan et al 2009).…”
Section: Discussionsupporting
confidence: 84%
“…The production of cloned mice from both ME and AE cytoplasts also support our previous findings on the beneficial effects of VPA treatments for mouse cloning in the B6CBAF1 strain (Costa-Borges et al 2010). These beneficial effects, corroborated in miniature pig SCNT embryos (Miyoshi et al 2010), have recently been questioned by Ono et al (2010), who compared the effects of different HDACis on cloning BD129F1 mice. The discrepancy of results in the mouse species can be probably attributed to strain-specific differences, as not all HDACis are equally effective in all genetic backgrounds (Kishigami et al 2007, Van Thuan et al 2009).…”
Section: Discussionsupporting
confidence: 84%
“…In other words, the present system using pOEIN transfectants would be useful for screening drugs supporting in vivo development of SCNT embryos. With this system, we have recently demonstrated that valproic acid, a histone deacetylase inhibitor, is beneficial for prolonged expression of Oct-3/4 as well as for increasing the blastocyst formation rates of SCNT embryos [59]. In addition, our system is helpful for establishment of ES cell lines by long-term serial passage of ICM-derived cells, since pluripotent-state ES cells can be simply and noninvasively monitored under a fluorescent microscope.…”
Section: Discussionmentioning
confidence: 99%
“…4C, lane 8) may be ascribed to failure to express their α-GalT mRNA at a level detectable by RT-PCR, as previously pointed out. This phenomenon may be related to the failure of proper reprogramming of donor nuclei after SCNT, since gene activation of embryonic and pluripotency-related genes is sometimes suppressed [43,44]. In our preliminary data, expression of α-GalT mRNA increased gradually with progression towards the blastocyst stage (unpublished results).…”
Section: Discussionmentioning
confidence: 67%